CHINESE PAINTINGS IN JIANG XI, CHINA: IMPACTING AND MARKET VALUE IN CONTEMPORARY ARTS - Tan yiqun; Gregory Anak Kiyai Keai (Journal of Islamic, Social, Economics and Development, 2024)
The present research investigates the dynamics around modern Chinese paintings in Jiangxi, China, with a specific emphasis on their influence and economic worth. This research also focuses on the modern artworks marketplace in order to get insights into the many aspects that influence their market value. This analysis explores the many aspects that impact the market value of an item, including elements such as workmanship, uniqueness, authenticity, and creative styles. The study adopts a multifaceted method, drawing on the rich artistic landscape of Jiangxi. The focus of this study is to the analysis of the many factors that impact the marketplace for Chinese artworks. The methodology used in this study adopts a mixed-methods approach, including the use of surveys and interviews as data collection tools to capture a wide range of opinions. The results of the study provide insights into customer behaviour, tastes, and market developments. The suggestions put forward by the research highlight the significance of attending to customer tastes and fostering creative ingenuity in order to augment the marketplace worth of modern artworks in Jiangxi, China.